INCREASE CUSTOMER LOYALTY THROUGH SERVICE QUALITY, AND TRUST - Aminnudin, Moch; Sofwan, Ali; Sarimaryoni, Hamdi (LP2M Universitas Bina Bangsa, 2025)
This study aims to analyze the influence of the variables Service Quality (X1), and Trust (X2), on the dependent variables of Customer Loyalty (Y) of J&T Express consumers in the Jepara branch. The respondents of the study were consumers who made purchases at J&T Express at the Jepara branch totaling 100 respondents. This study uses primary data by collecting data through observation with questionnaires. The data collection medology uses a survey using the accidental sampling method. The results of the multiple liner regression analysis had a positive relationship between the independent variable and the dependent variable. The result of the determination coefficient with an R square value of 91%, means that the model in this study can be explained by 91%, while the remaining 9% is explained by other variables outside the research model